Clinical use of DNA markers linked to the gene for Duchenne muscular dystrophy. Issue 3 (March 1984) - Pembrey, M E; Davies, K E; Winter, R M; Elles, R G; Williamson, R; Fazzone, T A; Walker, C
Abstract : Seventy families with Duchenne muscular dystrophy (DMD) known to the Institute of Child Health fall into three categories with respect to potential linkage analysis with the X chromosome DNA markers RC8 and L1.28 that bridge the DMD gene. Families in which there is at least one obligatory female heterozygote (n = 13). Here 'prediction' and 'exclusion' of DMD gene transmission may be possible, the accuracy being dependent on the closeness of the linkage of the DNA marker(s) to the DMD gene; an illustrative case is reported. Families in which there is a single affected boy, who also has one or more healthy brothers (n = 26). Given an informative restriction fragment length polymorphism (RFLP), the probability that the boy represents a new mutation can be reassessed; it is also possible to 'exclude' the DMD gene in a sister. Families with a single affected boy with no brother (n = 30). Here 'exclusion' of the DMD gene in a sister may be possible. Only in one family was there no possibility of useful linkage analysis. The linkage analysis required is described, and the need to check DMD families for informative RFLPs is stressed.